EXPLORING INDONESIAN PRE-SERVICE TEACHERS’ STRATEGIES DURING PRACTICUM IN THAI SCHOOLS - Nabila Muna Kusuma; Siti Nur'Aini; Theresia Cicik Sophia Budiman (University of Kuningan, 2025)
Teaching practicum is a component of teacher education programs that provides pre-service teachers (PST) with practical classroom experience. This study investigated the teaching strategies and challenges of Indonesian student teachers during practicum in Thai schools. The study involved 27 participants from 4 universities in Central Java who participated in a one-month internship program. Using qualitative methods, data were collected through open-ended questionnaires and interviews. All 27 participants agreed to complete open-ended questionnaires regarding the challenges experienced during the teaching practicum. From the results of the questionnaire, only 4 participants agreed to be interviewed further regarding teaching strategies. The results obtained from filling out the questionnaire about the challenges showed that 89% experienced language barriers, 8% were constrained in learning media, and 4% had difficulty finding halal food. On the other hand, the results obtained from interviews show that PST apply teaching strategies using digital media, printed media, and ice-breaking. Based on these findings, it can be concluded that the use of strategies in teaching must be appropriate and can make students understand the material presented by PST due to the limited language and media.Keywords: pre-service teachers; teachers’ strategies; challenges; teaching practicum.